Análise da estrutura de endividamento de PME Portuguesas: o caso específico do setor da construção - Gonçalves, Adriana Maria Pereira (2022)
The construction sector has a strong impact on the Portuguese economy and has been growing steadily in recent years. The capital structure of companies is a very relevant topic in the area of finance, since the form of financing influences the cost of capital and the value of the company. Despite the various studies conducted so far, the results obtained are not conclusive, so the literature has tried to understand which determinants explain the best capital structure. This paper studies the relationship between the capital structure of Portuguese SME in the construction sector and its determinants based on panel data models. To perform this study a database extracted from SABI is used, the same is composed of 5.389 firms, in a time horizon of 11 years. The theoretical and empirical framework was carried out through the financial theories of capital structure, then the determinants of the level of debt of companies were investigated, and the following were considered: size, profitability, tangibility, benefits beyond debt, growth, liquidity and risk. These determinants will have total debt, short term debt, and medium and long term debt as explained variables. The research uses the static panel data models, the estimation was done through the Ordinary Least Squares (OLS) model, the fixed effects model and the random effects model. The results obtained in the study indicate that the total and short-term debt ratio are positively influenced by the growth determinant, on the other hand they are negatively influenced by the profitability and tangibility determinants. However, the medium and long-term debt ratio is positively influenced by the determinants tangibility and growth, but is negatively influenced by the determinant profitability.